Strong Stubborn Sets for Efficient Goal Recognition Design - Keren, Sarah; Gal, Avigdor; Karpas, Erez (Proceedings of the International Conference on Automated Planning and Scheduling, 2018)
Goal Recognition Design (GRD) is the task of redesigning environments (either physical or virtual) to allow efficient online goal recognition. In this work we formulate the redesign problem as an optimization problem, aiming at early goal recognition. To this end, we use a measure of worst case distinctiveness (wcd), which represents the maximal number of steps an agent may take before his goal is revealed. With the objective ofminimizing wcd, we construct a search space in which each node in the space is a goal recognition model (one of which is the original model given as input) and one can move from one model to another by applying a model modification, chosen from a set of allowed modifications given as input. Our specific contribution in this work includes the specification of a class of modifications for which we can prune the search space using strong stubborn sets. Such positioning allows reducing the computational overhead of design while preserving completeness. We show that the proposed modification class generalizes previous works in goal recognition design and enriches the state-of-the-art with new modifications for which strong stubborn set pruning is safe. We support our approach by an empirical evaluation that reveals the performance gain brought by the proposed pruning strategy in different goal recognition design settings.